2015
DOI: 10.1007/s11356-015-4797-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural responses of soil N-cycling microbial communities to the herbicide mesotrione: a dose-effect microcosm approach

Abstract: Microbial communities driving the nitrogen cycle contribute to ecosystem services such as crop production and air, soil, and water quality. The responses to herbicide stress of ammonia-oxidizing and ammonia-denitrifying microbial communities were investigated by an analysis of changes in structure-function relationships. Their potential activities, abundances (quantitative PCR), and genetic structure (denaturing gradient gel electrophoresis) were assessed in a microcosm experiment. The application rate (1 × FR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 54 publications
(63 reference statements)
1
24
0
1
Order By: Relevance
“…Nevertheless, more subtle changes, e.g., in rare OTUs, may reflect adaptation of bacterial communities to a specific factor such as presence of a micropollutant or its degradation. This type of response, however, may not have to be proportional to exposure dose, and will thus likely be difficult to evidence at environmental concentrations, as shown previously for soil ( Crouzet et al, 2010 ). Worthy of note in the perspective of future studies, temporal trajectories of community changes during incubation may additionally evidence transient responses of groundwater bacterial diversity during MET degradation.…”
Section: Resultsmentioning
confidence: 96%
“…Nevertheless, more subtle changes, e.g., in rare OTUs, may reflect adaptation of bacterial communities to a specific factor such as presence of a micropollutant or its degradation. This type of response, however, may not have to be proportional to exposure dose, and will thus likely be difficult to evidence at environmental concentrations, as shown previously for soil ( Crouzet et al, 2010 ). Worthy of note in the perspective of future studies, temporal trajectories of community changes during incubation may additionally evidence transient responses of groundwater bacterial diversity during MET degradation.…”
Section: Resultsmentioning
confidence: 96%
“…After a microcosm study on a chernozem soil, no responses of the soil microbial communities (including N‐cycling and phototrophic communities) in terms of abundance, diversity, and activities were observed . These conclusions occurred for communities spread with both the environmental doses of pure and formulated (Callisto ® ) mesotrione.…”
Section: Effects Of Mesotrionementioning
confidence: 92%
“…Fumigants in general kill not only target pathogens but also off-target microorganisms that can be important in the soil microbial community. Microorganisms, and in particular bacteria, are reported to significantly influence the soil quality and crop yield by regulating several important soil processes, such as organic matter decomposition, organic pollutant degradation and nutrient transformation ( Álvarez-Martín et al, 2016 ; Crouzet et al, 2016 ). Previous studies reported that the fumigants chloropicrin (CP), 1,3-dichloropropene and metam sodium (MS) significantly decreased soil bacterial diversity and significantly changed the predominance of bacterial phyla in microbial communities ( Liu et al, 2015 ; Li et al, 2017a , b ; Zhang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%